Land marketization, secondary land market, and effects on industrial land price - Fan Tu; Shuangling Zou; Siwen Hu; Shinan Zhang (International Journal of Strategic Property Management, 2022)
Land marketization and its effects are widely documented across developing countries. Few studies, however, have investigated the link between industrial land price determination and industrial land market reform, based on the establishment of a pilot open trading platform for the secondary market. Moreover, no studies have specifically examined the link between primary and secondary industrial land markets. This study, therefore, investigates industrial land price determination using a quasi-natural experiment to interpret distortions in industrial land prices in China. Using industrial land sales data for 2006–2017 in the city of Haining, Zhejiang Province, China, this study compares industrial land value in the secondary market with land transfer prices in the primary market and identify undervaluation in the primary market. The results show that the growth rate of industrial land transfer prices increased every year after the open trading platform was established. Moreover, compared with nonpilot districts and counties, industrial land prices in the pilot city (Haining) increased by 11.14% from 2015 to 2017. The findings suggest that, based on the pilot program, further market reforms should be undertaken by establishing open trading platforms in a broader area.